PERANCANGAN SISTEM PELAPORAN PENYAKIT OLEH PUSKESMAS DALAM PENINGKATAN INFORMASI KESEHATAN DI KOTA PEKANBARU - Handoko, Bobi; Yuna, Tasya; Tonis, Marian; Zaky, Abdul (LPPM Universitas Awal Bros, 2024)
Pekanbaru City has 21 community health centers (Puskesmas), whose distribution influences the spread of diseases, including communicable, non-communicable, and chronic diseases. This study aims to design a web-based prototype to assist Puskesmas in routinely reporting disease data to the Pekanbaru City Health Office and to provide public access to disease information. A quantitative experimental method with a development research design was used. Data on the most prevalent diseases were collected through observation and documentation, then processed into a database. The research was conducted from January 31 to June 3, 2024. The resulting prototype was developed using PHP, HTML, CSS, and JavaScript, and is accessible via smartphones. Functional and feasibility tests confirmed the system works properly and is ready for use. This disease reporting and information system helps streamline data submission by Puskesmas and enhances public access to health information. It is recommended that the local government support its development and implementation across all Puskesmas in Pekanbaru.